2012
DOI: 10.3945/jn.112.160077
|View full text |Cite
|
Sign up to set email alerts
|

Ruminant-Produced trans-Fatty Acids Raise Plasma HDL Particle Concentrations in Intact and Ovariectomized Female Hartley Guinea Pigs

Abstract: Cardiovascular disease (CVD) is the leading cause of death among women worldwide, and risk for developing CVD increases postmenopause. Consumption of trans-fatty acids (tFA) has been positively associated with CVD incidence and mortality. The current study was designed to assess the effects of diets high in industrially produced (IP)-tFA, from partially hydrogenated vegetable oils (PHVO), and ruminant-produced (RP)-tFA, from butter oil (BO), on risk factors for CVD. Thirty-two female Hartley guinea pigs, one-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…There are two sources of dietary TFA: (i) industrial TFA, which are produced technologically during the partial hydrogenation of vegetable oils; and (ii) ruminant TFA, such as vaccenic acid and conjugated linoleic acid (CLA) that are synthesized by rumen bacteria via the metabolism of MUFA and PUFA ( 7 9 ) . Clinical studies have reported that dietary intake of industrial TFA has a deleterious effect on lipoprotein concentrations; however, ruminant TFA may be less detrimental to blood lipid levels than industrial TFA ( 10 ) .…”
mentioning
confidence: 99%
“…There are two sources of dietary TFA: (i) industrial TFA, which are produced technologically during the partial hydrogenation of vegetable oils; and (ii) ruminant TFA, such as vaccenic acid and conjugated linoleic acid (CLA) that are synthesized by rumen bacteria via the metabolism of MUFA and PUFA ( 7 9 ) . Clinical studies have reported that dietary intake of industrial TFA has a deleterious effect on lipoprotein concentrations; however, ruminant TFA may be less detrimental to blood lipid levels than industrial TFA ( 10 ) .…”
mentioning
confidence: 99%
“…Penelitian lain yang dilakukan oleh Almeida (2019) bahwa minyak ikan mengandung asam palmitat (C16:0) yang berfungsi sebagai penyuplai asam vaccenic yang merupakan prekursor utama CLA (conjugated linoleic acid) sebagai penyebab menurunnya kolesterol darah. CLA adalah grup isomer dari asam linoleat yang mempunyai kapasitas untuk melakukan beberapa manfaat terhadap metabolisme, seperti penghambatan lipogenesis, kolesterol darah dan pengurangan insiden kanker, serta perubahan pertumbuhan jaringan otot (Onakpoya et al, 2012;Rice et al, 2012).…”
Section: Kolesterol Darahunclassified
“…Vaccinic acid (C18:1ω7) was increased numerically (p=0.36) in blood plasma (Table 7) and in milk (p= 0.25) (Table 8) with beads supply compared to control goats (1.17 vs. 0.8) in blood and (0.30 vs. 0.22) in milk, respectively indicating an incomplete biohydrogenation by microbial activity (Corl et al, 2001). Also, vaccinic acid is known as the main precursor of conjugate linoleic acid (CLA), which is an isomers group of linoleic acid that has the capacity to perform several metabolic benefits in human as inhibition of lipogenesis, blood cholesterol, cancer incidence reduction and changes in muscle tissues growth (Rice et al, 2012). Almeida et al (2019) found the same trend of the present results with fish oil supplemented to goats and also, oleic acid was increased (P<0.01) in milk in the same group.…”
Section: Monounsaturated Fatty Acids (Mufa)mentioning
confidence: 99%